PENDIDIKAN KARAKTER DI PONDOK PESANTREN MODERN PALANGKARAYA - Zainatur Rahmah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This study aims to determine and describe the implementation of character education in modern pesantren. The benefit is to provide knowledge and enrich scientific insight for researchers and for readers about character education. This research is field research with a qualitative approach. Data collection methods used are  observation,              interviews,         and       documentation. Researchers       used              data triangulation to see the validity of the data. While the data analysis used is the technique of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of character education in the Modern Pondok Pesantren Darul Ulum Palangka Raya instills character values, including religious character values, independence, discipline, responsibility, love of knowledge, courtesy, honesty, tolerance (tasamuh), and love of the land. Please assist (ta'awun).The application of these character values uses the yellow book teaching method, habituation of daily religious activities, and the example of kyai and ustadz.